Pearkes, George Randolph: my political recollections (May 1, 1968) - http://id.worldcat.org/fast/1970190; Roy, Reginald H. and Neil Swainson (1968)
ABSTRACT: Maj-Gen. Pearkes, 1 May, 1968. 24pp. By Dr. R.H. Roy and Dr. Neil Swainson. Anecdote. Involvement in provincial politics, 1940/50's. Relationship to federal politics. Some provincial and federal political personalities..; Interviewer: Roy, Reginald H. and Neil Swainson; Rank: Major-General. Medals and Honours: Victoria Cross (VC); Order of Canada (CC); Companion of the Bath (CB); Distinguished Service Order (DSO); Military Cross (MC); Canadian Forces Decoration (CD); Interviewee: Pearkes, George Randolph, 1888-1984; An interview/narrative of George Randolph Pearkes's political recollections. Major-General Pearkes, V.C., C.C., C.B., D.S.O., M.C., C.D. was a Member of Parliament from 1945-1960. Interview took place on May 1, 1968.